HUBUNGAN OLAHRAGA DENGANKEJADIAN ULKUS KAKI DIABETIK PADA PASIEN DIABETES MELITUS: HUBUNGAN OLAHRAGA DENGANKEJADIAN ULKUS KAKI DIABETIK PADA PASIEN DIABETES MELITUS - rezi prima; Sisca Oktarini (LPPM Universitas Abdurrab, 2024)
The most important chronic complication of diabetes mellitus is neuropathy, the result of which is the appearance of diabetic foot ulcers. The risk of developing diabetic foot ulcers is very large in individuals who have do not exercise well and take poor foot care. The aim of this study is to determine the risk factors associated with the occurrence of diabetic foot ulcers in diabetes mellitus patients in Hospital Inpatient Room. Descriptive Analytical research design with a Cross Sectional approach. The population of this study was 91 Diabetes Mellitus patients using the Accidental Sampling sampling technique with a total sample of 47 people. Data collection was carried out using questionnaires and patient documentation studies. Then it is processed using univariate and bivariate analysis. The results of the study showed that, 46.8% had poor body exercise, and 51.1% of diabetic foot ulcers. as much as 59.6%. Based on the results of this study, it can be concluded that there is a significant relationship between poor bodyexercise to foot ulcers, The researcher's suggestion is for respondents to know what causes diabetic foot ulcers.